Antioxidant, antiglycation, and anti-inflammatory activities of Caesalpinia mimosoides - Rodwattanagul, Soraya; Nimlamool, Wutigri; Okonogi, Siriporn (Drug Discoveries & Therapeutics, 2023)
Oxidative stress, glycation and inflammation are the main causes of many severe diseases. To date, no single extract has been shown to simultaneously inhibit these three reactions. In this study, the antioxidant, antiglycation and anti-inflammatory activities of ethanol extracts from four edible plants that are commonly used as Thai folk medicine were compared. Among these extracts, Caesalpinia mimosoides extract (CME) showed the highest antioxidant potential with Trolox equivalent antioxidant activity (TEAC) of 5.9 ± 0.1 mM/mg followed closely by Zingiber officinale extract (ZOE) with a TEAC value of 5.4 ± 0.2 mM/mg. However, CME showed no cytotoxicity, whereas ZOE greater than 60 μg/mL showed cytotoxicity to normal human cells. Antiglycation assay using bovine serum albumin-ribose showed comparable potency between CME and Spondias dulcis extract (SDE). However, CME exhibited a high anti-inflammatory activity, significantly higher than SDE and activity depending on the dose. At a concentration of 60 μg/mL, approximately 85% of the interleukin-6 pro-inflammatory cytokine produced from human monocytes, induced by lipopolysaccharides, was completely inhibited by CME whereas SDE showed no inhibition. In summary, CME is the most potential extract with simultaneously activity of these three reactions. CME has the highest total phenolic content expressed as gallic acid equivalent to 301 ± 8 mg/g. Identification using high-performance liquid chromatography revealed the presence of at least four phenolic compounds, gallic acid, syringic acid, p-coumaric acid, and ellagic acid are existed in CME. Our finding suggests that CME is a promising natural source for inhibition of oxidative stress, glycation, and inflammation.